Teachers’ Strategies in Giving Feedback on Students’ Speaking Performance - Nurpianti Nurpianti (Journal of English Education and Linguistics, 2020)
This research was done because the researcher found several problems in teaching and learning speaking at school. The problems that the researcher found:Due to this phenomenon, the researcher wants to know about Teachers’ strategies in giving feedback on students speaking performance eleventh grade in SMAN 1 Canduang. The design of this research as descriptive qualitative. The informant of the research were the English teacher and the students at the eleventh grade in SMAN 1 Canduang. The researcher focused to class eleventh grade majoring in social 2. While techniques of data collection were observation and interview.The findings reveals that is teachers strategy in giving feedback on students speaking performance: feedback on the content, feedback on form, feedback during oral work, feedback during accuracy work, feedback during fluency work.